Prophylactic percutaneous endoscopic gastrostomy in patients with head and neck cancer: Influence on nutritional status, utilisation rate and complications. Issue 11 (13th September 2019) - Hausmann, Johannes; Kubesch, Alica; Müller von der Grün, Jens; Goettlich, Carmen M.; Filmann, Natalie; Oliver Tal, Andrea; Vermehren, Johannes; Friedrich‐Rust, Mireen; Wächtershäuser, Astrid; Bojunga, Jörg; Blumenstein, Irina
Abstract: Background: Patients with head and neck cancer (HNC) are at high risk for malnutrition because of tumour localisation and therapy. Prophylactic percutaneous endoscopic gastrostomy (PEG) tube placement is common practice to prevent malnutrition. Objective: To investigate the benefits of prophylactic PEG tube placement for HNC patients in terms of the influence on patients' nutritional status, utilisation rate, complications and to identify the predictors of PEG tube utilisation. Methods: All consecutive HNC patients who underwent prophylactic PEG tube insertion between 1 January 2011 and 31 December 2012 prior to therapy were enrolled. The PEG tube utilisation rate, complications, the patients' nutritional status and tumour therapy were evaluated with the help of electronic patient charts and telephone interviews. Results: A total of 181 patients (48 female, median 67.5 years) were included. The PEG utilisation rate in the entire cohort was 91.7%. One hundred and forty‐nine patients (82.3%) used the PEG tube for total enteral nutrition, 17 patients (9.4%) for supplemental nutrition and 15 patients (8.3%) made no use of the PEG tube. Peristomal wound infections were the most common complications (40.3%) in this study. A high Nutritional Risk Screening (NRS) score prior to tube insertion was found to be independently associated with PEG utilisation. No significant weight changes were observed across the three patient subgroups. Conclusions: The overall PEG tube utilisation rate was high in this study. However, given the high rate of infections, diligent patient selection is crucial in order to determine which patients benefit most from prophylactic PEG tube insertion.